A Standard Procedure for In Vitro Digestion Using Rumen Fermenters: A Collaborative Study - Larissa Frota Camacho; Tadeu Eder da Silva; João Paulo Pacheco Rodrigues; Marcia de Oliveira Franco; Edenio Detmann (Animals, 2022)
Our objective was to propose and evaluate a standard procedure for the evaluation of in vitro dry matter digestibility for ruminant feeds, using artificial fermenters. A collaborative study was performed with seven feed analysis laboratories and four feeds (Tifton 85 hay, corn silage, soybean hulls, and soybean meal). Two types of artificial fermenters were evaluated (DaisyII Ankom and TE-150 Tecnal). Each laboratory received 80 sealed filter bags with samples (20 per feed), eight blank filter bags, a plastic bag with buffer solution reagents, and instructions describing how to conduct a 48 h in vitro assay using an artificial fermenter and how to collect bovine ruminal inoculum. On average, the contribution of laboratory effect to the total random variance was 24%, being less than the contribution of equipment (42%) and error (34%). The repeatability ranged from 3.34 to 5.79%, across feeds. The reproducibility ranged from 5.93 to 8.94% across feeds, which implied Horwitz ratios ranging from 2.94 to 4.10. Due to the specific characteristics of the analytical entity evaluated here, which is defined by the method itself, the proposed method was considered reproducible. The results highlighted that, if the method is followed exactly, its results are precise and present adequate levels of repeatability and reproducibility.